1984
DOI: 10.9753/icce.v19.167
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetric Monitoring of Dolos Stability, Manasquan Inlet, New Jersey

Abstract: Photogrammetry has been applied as a technique to monitor the stability of dolosse on the Manasquan Inlet, New Jersey jetties. These jetties were rehabilitated between 1979 and 1982 with 16-ton steel-reinforced dolosse. The jetties have been exposed to a number of storms since 1982, including a design-level storm in March 1984. The photogrammetric measurements have provided a detailed record of the magnitude and direction of dolos movements in response to these storm events. Standard leveling techniques have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While breakage has typically been associated with some amount of movement, either of the dolos which breaks or of adjacent units, it has not necessarily been associated with significant movement and vice versa. At the Manasquan Inlet jetties, Gebert and Clausner (1984) also observed that the largest displacements experienced were by dolosse which did not break. The dolosse at Manasquan Inlet weigh 14.6 metric tons (16 tons).…”
Section: Breakagementioning
confidence: 80%
See 3 more Smart Citations
“…While breakage has typically been associated with some amount of movement, either of the dolos which breaks or of adjacent units, it has not necessarily been associated with significant movement and vice versa. At the Manasquan Inlet jetties, Gebert and Clausner (1984) also observed that the largest displacements experienced were by dolosse which did not break. The dolosse at Manasquan Inlet weigh 14.6 metric tons (16 tons).…”
Section: Breakagementioning
confidence: 80%
“…To date, the dominant dolos movement has been upslope with slight settling plus rotation about the vertical or z-axis (yaw). Yaw was also the predominant dolos rotation observed by Gebert and Clausner (1984) at the Manasquan Inlet jetties. This type of rotation probably occurs more frequently because the upper layer dolosse are not constrained laterally as much as they are vertically; note that the settlement shown in Table I is a relatively small component of the total translation experienced.…”
Section: Figurementioning
confidence: 85%
See 2 more Smart Citations